2021
DOI: 10.3390/microorganisms9102150
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergism of Penicillin and Ceftriaxone against Enterococcus faecalis

Abstract: Enterococcus faecalis infective endocarditis is commonly treated with intravenous ampicillin/ceftriaxone combination therapy. Ampicillin, however, is unsuitable for outpatient parenteral antibiotic therapy (OPAT) regimens due to its instability in 24 h continuous infusors, and has been successfully replaced by benzylpenicillin used together with ceftriaxone in a few small case series. Since in vitro synergy data of penicillin/ceftriaxone against E. faecalis are still lacking, checkerboard assays were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Only one other in vitro study has been published to date, which also compared checkboard synergy of ampicillin+ceftriaxone versus penicillin+ceftriaxone among 28 clinical E. faecalis blood isolates from Germany and one wild-type isolate (ATCC 29212) ( 19 ). The ceftriaxone concentrations utilized included the free plasma trough concentrations for a 2 g IV q12h, 4 g IV q24h, and 2 g IV q24h regimens, which were 4, 1.5, and 1 μg/L, respectively ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one other in vitro study has been published to date, which also compared checkboard synergy of ampicillin+ceftriaxone versus penicillin+ceftriaxone among 28 clinical E. faecalis blood isolates from Germany and one wild-type isolate (ATCC 29212) ( 19 ). The ceftriaxone concentrations utilized included the free plasma trough concentrations for a 2 g IV q12h, 4 g IV q24h, and 2 g IV q24h regimens, which were 4, 1.5, and 1 μg/L, respectively ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only one other in vitro study has been published to date, which also compared checkboard synergy of ampicillin+ceftriaxone versus penicillin+ceftriaxone among 28 clinical E. faecalis blood isolates from Germany and one wild-type isolate (ATCC 29212) ( 19 ). The ceftriaxone concentrations utilized included the free plasma trough concentrations for a 2 g IV q12h, 4 g IV q24h, and 2 g IV q24h regimens, which were 4, 1.5, and 1 μg/L, respectively ( 19 ). Conversely, we utilized a free steady-state plasma concentration of 17.2 μg/mL based on clinical pharmacokinetic data for a 2 g IV q12h regimen, where the extrapolated trough would be 9.13 μg/mL versus the 4 μg/mL utilized by Thieme et al ( 19 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, it has been assumed that the synergistic activity exhibited by AC [ 14 , 15 ] is preserved in BC combination [ 20 ]. However, recent studies have shown poor correlation between AC and BC synergistic activity and lower rates of this interaction with BC in E. faecalis clinical strains [ 21 , 22 ]. Secondly, ceftriaxone dose regimen adjustment for OPAT entails the same difficulty shown in the AC regimen.…”
Section: Discussionmentioning
confidence: 99%